Red Yeast Rice as a natural source of Monacolin K – the efficacy among patients with dyslipidemia. A literature review - Simlat, Aleksandra; Sado, Aleksandra; Lisik, Bartłomiej; Skowierzak, Filip; Kozyra, Klaudia; Kozieł-Kwit, Sylwia; Rogowska, Wiktoria; Szada-Borzyszkowski, Krzysztof; Wręczycki, Mariusz; Sawczuk, Kacper (Journal of Education, Health and Sport, 2026)
Background: Dyslipidemia is a common disease worldwide associated with increased cardiovascular risk. It is associated with many possible health consequences. An important issue in the treatment of dyslipidemia is lifestyle modification. Moreover, the use of nutraceuticals and pharmacological treatment is equally important. Red yeast rice contains monacolin K, which can reduce plasma levels of low-density lipoprotein cholesterol and total cholesterol. Moreover, contains gamma-aminobutyric acid, which has antihyperlipidemic effects. Aim: This article aims to review current evidence on the effectiveness of the treating of dyslipidemia with Monacolin K, which is contained in Red Yeast Rice. Material and Methods: A literature review was conducted from the PubMed and Google Scholar databases. Key phrases as “red yeast rice”, “monacolin K” and “LDL-cholesterol” were used. Results and conclusion: Supplementation with a low daily dose of red yeast rice, which contains Monacolin K can reduce the risk of cardiovascular diseases among patients with dyslipidemia by lowering plasma levels of low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC).